2009
DOI: 10.1186/1475-2875-8-103
|View full text |Cite
|
Sign up to set email alerts
|

Development of vegetable farming: a cause of the emergence of insecticide resistance in populations of Anopheles gambiae in urban areas of Benin

Abstract: BackgroundA fast development of urban agriculture has recently taken place in many areas in the Republic of Benin. This study aims to assess the rapid expansion of urban agriculture especially, its contribution to the emergence of insecticide resistance in populations of Anopheles gambiae.MethodsThe protocol was based on the collection of sociological data by interviewing vegetable farmers regarding various agricultural practices and the types of pesticides used. Bioassay tests were performed to assess the sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(152 citation statements)
references
References 13 publications
8
143
0
Order By: Relevance
“…The Akron colony from Benin has low level DDT resistance (LT 50 ∼ 1 h) and some kdr mutations, but at lower frequencies than the Ghanaian population [frequency (kdr): Ghanaian M-form 0.58, Akron M-form colony 0.29]. The Akron colony was established in June 2008 at around the same time that Yadouleton et al were assessing DDT susceptibility in the same location (53). In the latter study far higher levels of DDT resistance were observed (15% mortality following a WHO tube assay).…”
Section: Methodsmentioning
confidence: 99%
“…The Akron colony from Benin has low level DDT resistance (LT 50 ∼ 1 h) and some kdr mutations, but at lower frequencies than the Ghanaian population [frequency (kdr): Ghanaian M-form 0.58, Akron M-form colony 0.29]. The Akron colony was established in June 2008 at around the same time that Yadouleton et al were assessing DDT susceptibility in the same location (53). In the latter study far higher levels of DDT resistance were observed (15% mortality following a WHO tube assay).…”
Section: Methodsmentioning
confidence: 99%
“…Reporting permethrin resistance rates of 24-82 % in A. gambiae populations from city vegetable farms in Ghana, Yadouleton et al (2009) claimed to have demonstrated that urban agriculture led to resistance development. Unfortunately, resistance was not tested for populations in areas where no urban vegetable production took place, and this lack of control sites and information on background resistance levels mean that it is impossible to ascribe the cause to urban agriculture.…”
Section: Malaria and Urban Agriculturementioning
confidence: 99%
“…This is due to their relatively low mammalian toxicity and rapid knockdown effect that cause paralysis of an insect. Pyrethroids are also used in agriculture to control crop pests and this intensive use has led to reports of reduced efficacy [5] [6].…”
Section: Introductionmentioning
confidence: 99%